Strategy and Management Accounting Practices Alignment and Its Effect on Organizational Performance - Sherine Farouk Abdel Al; John D. McLellan (Journal of Accounting, Business and Management (JABM), 2013)
Purpose - We study the effect on performance by the degree of fit between the various management accounting practices that an organization employs and the strategy pursued by that organization. It is postulated that, The more that the management accounting practices adopted by an organization are aligned with strategic objectives of that organization, the greater the business performance. Design/methodology/approach - Two hundred and fifteen manufacturing companies are studied. Data was collected through a four part structured questionnaire relating to a firm's characteristics, the adoption of 42 management accounting practices, the firm's strategic priorities and the organization's overall performance. Findings - This study provides empirical data in support of contingency theory's central proposition that organizational performance depends on the fit between organizational context and structure. If an organization has a good alignment between management accounting practices and strategy employed, this fit has both a positive and significant affect on operational performance. Prior research studies (Govindarajan, 1988; Kathuria and Porth 2003 and Jermias and Gani, 2004) have argued that the fit between management accounting practices and strategic priorities will have a positive relationship on performance. That argument is supported by the results of this research. Research implications - Management accounting practices do not differ from one industry to another, but rather from one strategy to another. Therefore, the type of industry does not have an impact on the type of management accounting practices adopted; it is the type of strategy that must be supported with specific management accounting practices that has an impact on performance. Practical implications - The findings of this study should increase the understanding of how different strategic priorities require different organizational configurations to affect positively the performance of manufacturing organizations.